2021
DOI: 10.1021/acs.jpcb.1c00972
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Native Ensembles Dictate the Differential Functional Responses of Nuclear Receptor Ligand-Binding Domains

Abstract: Native states of folded proteins are characterized by a large ensemble of conformations whose relative populations and interconversion dynamics determine the functional output. This is more apparent in transcription factors that have evolved to be inherently sensitive to small perturbations, thus fine-tuning gene expression. To explore the extent to which such functional features are imprinted on the folding landscape of transcription factor ligand-binding domains (LBDs), we characterize paralogous LBDs of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…The nature and the strength of ligand binding (which is effectively a perturbation to the binding site) could therefore determine the functional output by restricting the accessible conformational space as seen in the energy landscapes of activated receptors. A similar conformational feature has been recently demonstrated in the diverse class of large nuclear receptor ligand binding domains, 55 indicating that ‘conformational selection’ and subsequent enthalpic compensation (via drug-protein contacts or GPCR-G-protein interactions) of entropic stability could be generic features underlying the energy landscapes of proteins and, hence, function.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The nature and the strength of ligand binding (which is effectively a perturbation to the binding site) could therefore determine the functional output by restricting the accessible conformational space as seen in the energy landscapes of activated receptors. A similar conformational feature has been recently demonstrated in the diverse class of large nuclear receptor ligand binding domains, 55 indicating that ‘conformational selection’ and subsequent enthalpic compensation (via drug-protein contacts or GPCR-G-protein interactions) of entropic stability could be generic features underlying the energy landscapes of proteins and, hence, function.…”
Section: Discussionsupporting
confidence: 61%
“…Such a 2D landscape has been particularly successful in capturing functionally relevant substates in multiple large water-soluble proteins. 42,54,55 For example, consider the free-energy landscapes of Rhodopsin (GPCR1), the β 2 AR (GPCR3) and the Kappa-type opioid receptor (GPCR8) at 310 K (Figure 3). The native ensembles are broad in the GPCRs considered, but with differences in the extent and nature of structure.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the model can be found in earlier works. Briefly, the WSME model discretizes the phase space accessible to a protein chain by assuming that every residue can sample either folded-like (binary variable 1 ) or unfolded-like (binary variable 0 ) conformations. The microstates will therefore be represented by strings of ones and zeros.…”
Section: Methodsmentioning
confidence: 99%
“…The free-energy landscapes obtained by the WSME model can be combined with Monte Carlo simulations using the Metropolis algorithm to simulate single-molecule trajectories and examine microscopic protein-folding kinetics [ 42 , 45 , 53 , 65 , 71 , 72 , 87 , 88 , 106 , 111 , 112 ]. Since the WSME model is a Gō-type coarse-grained model with a limited number of possible conformations, simulations of protein-folding reactions can be performed with low computational complexity.…”
Section: Prediction Of Folding Mechanismsmentioning
confidence: 99%
“…In the previous sections, we showed that the folding mechanisms of small single-domain proteins are described well by the WSME model. By contrast, the folding mechanisms of multi-domain proteins have been less frequently studied because they have complex, multiple folding pathways and intermediates, making it difficult to theoretically predict the folding processes [ 53 , 75 , 78 , 81 , 91 , 106 , 108 , 112 , 113 , 114 , 115 , 116 ]. However, multi-domain proteins comprise the majority of the proteome, and more than 70% of eukaryotic proteins contain multiple domains [ 117 , 118 ].…”
Section: Folding Mechanisms Of Multi-domain Proteinsmentioning
confidence: 99%